2019
DOI: 10.3389/fped.2019.00096
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Availability in Respiratory Muscles During Exercise in Children Following Fontan Operation

Abstract: Introduction: As survival of previously considered as lethal congenital heart disease forms is the case in our days, issues regarding quality of life including sport and daily activities emerge. In patients with Fontan circulation, there is no pump to propel blood into the pulmonary arteries since the systemic veins are directly connected to the pulmonary arteries. The complex hemodynamics of Fontan circulation include atrial function, peripheral muscle pump, integrity of the atrioventricular valve,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 35 publications
(47 reference statements)
0
8
0
2
Order By: Relevance
“…Oxygen consumption. Reported mean VO 2peak values ranged from 14.4 AE 6.1 mL/kg/min 17 to 35.97 AE 6.84 mL/kg/min, 18 and mean percent-predicted VO 2peak values ranged from 54.3% AE 9.2% 19 to 86% AE 19% 20 (Table 1). Multiple studies reported significantly lower VO 2peak , 17,18,[21][22][23][24] VO 2 at anaerobic threshold, 17,23,25 and O 2 pulse 17,21 relative to healthy individuals.…”
Section: Cardiovascular Response and Exercise Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen consumption. Reported mean VO 2peak values ranged from 14.4 AE 6.1 mL/kg/min 17 to 35.97 AE 6.84 mL/kg/min, 18 and mean percent-predicted VO 2peak values ranged from 54.3% AE 9.2% 19 to 86% AE 19% 20 (Table 1). Multiple studies reported significantly lower VO 2peak , 17,18,[21][22][23][24] VO 2 at anaerobic threshold, 17,23,25 and O 2 pulse 17,21 relative to healthy individuals.…”
Section: Cardiovascular Response and Exercise Capacitymentioning
confidence: 99%
“…Reported mean VO 2peak values ranged from 14.4 AE 6.1 mL/kg/min 17 to 35.97 AE 6.84 mL/kg/min, 18 and mean percent-predicted VO 2peak values ranged from 54.3% AE 9.2% 19 to 86% AE 19% 20 (Table 1). Multiple studies reported significantly lower VO 2peak , 17,18,[21][22][23][24] VO 2 at anaerobic threshold, 17,23,25 and O 2 pulse 17,21 relative to healthy individuals. Although reductions in both maximal and submaximal exercise capacity have been reported, 26 submaximal exercise parameters are typically less reduced than those for maximal exercise.…”
Section: Cardiovascular Response and Exercise Capacitymentioning
confidence: 99%
“…para realizar CPET 15 protocolo utilizado previamente por nuestro grupo de investigación (Figura 1b) 18 . Vastus-Laterallis (Figura 2b), la asociación fue débil (rho=0.28), y por tanto, es necesario aumentar el número de pacientes evaluados para sostener que el incremento en el WOB es la principal limitación muscular al ejercicio en PCF, y no así el factor muscular periférico 13 .…”
Section: Métodosunclassified
“…Utilizando esta tecnología, en PCF se ha evaluado la SmO 2 en m.Vastus-Laterallis encontrando una disminución total de la oxigenación posterior al ejercicio físico máximo (∆SmO 2 = 4.5±2.1%) 12 . Hallazgo similar se ha reportado recientemente en m.Serratus-Anterior (∆HHb= 48±5%), en donde además se encontró asociación directa con el rendimiento físico (VO 2 -peak) 13 . Considerando los resultados de estos estudios, se infiere que durante el esfuerzo físico intenso, como ocurre en la valoración del test cardiopulmonar (Cardiopulmonary Exercise Testing, CPET), los PCF presentan incrementos del trabajo muscular locomotor y respiratorio, reflejado en la desoxigenación de m.Vastus-Laterallis y m.Serratus-Anterior.…”
Section: Introductionunclassified
“…The Fontan procedure is a palliative surgical strategy for patients with functional single ventricle malformations. The Fontan circulation is characterized by a non-pulsatile pulmonary blood flow leading to increased central venous pressure and low cardiac output and a series of physiologic changes typical for the univentricular circulation (1)(2)(3). Treatment and care of patients with univentricular heart defects has undeniably made great progress in recent years.…”
Section: Introductionmentioning
confidence: 99%